ACUTE TRACHEAL INJURY - Khalikov , S.P.; Karimov , M.R.; Butaev , L.A.; Holmamatov , H.T.; Ahadov , M.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
The article presents the definition of the concept of various types of damage to the respiratory tract, the mechanisms of their development, the principles of first aid and the choice of surgical treatment tactics, taking into account the nature of the injury and its localization. The technique of surgical restoration of the integrity of the breathing tube, the features of anesthetic and endoscopic support are described. Only timely diagnosis, adequate surgical and anesthetic care can ensure a favorable outcome in the treatment of this contingent of seriously ill patients.